Technical and Vocational Education and Training (TVET): What Next? (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
Employment sector has been invariably affected in the current crisis resulted from the global pandemic of COVID-19. This demands a paradigm shift in the present way of intervention in the TVET sector of Nepal through short- and long-term strategies.